Qualitative assessment of healthy volunteer experience receiving subcutaneous infusions of high-dose benzathine penicillin G (SCIP) provides insights into design of late phase clinical studies - Stephanie L. Enkel; Joseph Kado; Thel K. Hla; Sam Salman; Julie Bennett; Anneka Anderson; Jonathan R. Carapetis; Laurens Manning (PLoS ONE, 2023)
Introduction Secondary prophylaxis to prevent rheumatic heart disease (RHD) progression, in the form of four-weekly intramuscular benzathine benzylpenicillin G (BPG) injections, has remained unchanged since 1955. Qualitative investigations into patient preference have highlighted the need for long-acting penicillins to be delivered less frequently, ideally with reduced pain. We describe the experience of healthy volunteers participating in a phase-I safety, tolerability and pharmacokinetic trial of subcutaneous infusions of high-dose benzathine penicillin G (BPG)–the SCIP study (Australian New Zealand Clinical Trials Registry ACTRN12622000916741). Methods Participants (n = 24) received between 6.9 mL to 20.7 mL (3–9 times the standard dose) of BPG as a single infusion into the abdominal subcutaneous tissues via a spring-driven syringe pump over approximately 20 minutes. Semi-structured interviews at four time points were recorded, transcribed verbatim and thematically analysed. Tolerability and specific descriptors of the experience were explored, alongside thoughts on how the intervention could be improved for future trials in children and young adults receiving monthly BPG intramuscular injections for RHD. Results Participants tolerated the infusion well and were able describe their experiences throughout. Most reported minimal pain, substantiated via quantitative pain scores. Abdominal bruising at the infusion site did not concern participants nor impair normal activities. Insight into how SCIP could be improved for children included the use of topical analgesia, distractions via television or personal devices, a drawn-out infusion time with reduced delivery speed, and alternative infusion sites. Trust in the trial team was high. Conclusion Qualitative research is an important adjunct for early-phase clinical trials, particularly when adherence to the planned intervention is a key driver of success. These results will inform later-phase SCIP trials in people living with RHD and other indications.